Surgical Management and Functional Outcome of Acetabular Fractures – A Prospective Study - Sahu, Santosh K.; Reddy, Srujan; Nayak, Satya Prasanna; Kar, Dattatreya (Nigerian Journal of Basic and Clinical Sciences, 2024)
ContextAcetabulum fractures are commonly a result of high-velocity road traffic accidents and falls from height. These fractures were previously treated nonoperatively which had led to high morbidity causing secondary osteoarthritis, limping, instability, and chronic pain.AimsTo surgically manage the functional outcome of acetabular fractures.Settings and DesignThe prospective study involves 28 patients of a tertiary care hospital at Bhubaneswar, for analysis of functional and radiological outcomes of surgical management of acetabular fractures.Subjects and MethodsPatients are chosen from emergency and outpatient on the criteria of age group 18–65 years, pelvi-acetabular fractures of 2-mm displacement, more than 3-week-old fracture, with or without hip dislocation. Inflammatory arthritis and pathological fractures patients were excluded.Surgery time was 173 min with a minimum of 110 min and a maximum of 240 min.Statistical Analysis UsedAll the data were analyzed using SPSS 20 software.ResultsTwelve patients had excellent (42%), seven patients had well (25%), seven patients had fair (25%), and two patients had poor (8%) functional outcomes. Two patients had restricted range of movement and pain on walking and had undergone total hip replacement after 1 year.The mean score in the anatomically reduced fracture is 16.4, imperfectly reduced is 14.4, and poorly reduced is 8. The average functional outcome score was 14.2 (range – 5–18).ConclusionsAs the articular surface requires smooth congruity, anatomical fixation of fracture fragments is essential for early mobilization and better functional outcomes. Proper preoperative planning, anatomical reduction, adequate fixation, and early mobilization are required to achieve good functional outcomes in acetabular fractures.
Keywords: Acetabulum fracture; anatomic reduction; internal fixation; open reduction